Regulated competition under increasing returns to scale - Greve, T.; Keiding, H. (Journal of Public Economic Theory, 2016)
In the classical models of regulation economics, a mechanism that secures truthful revelation involves paying a subsidy to the firm. In this paper, we investigate whether it is possible to create a regulatory mechanism under a no‐subsidy constraint that induces the firm to report its private information truthfully. We consider a number of firms operating under regulated competition and with increasing returns to scale technology. It is shown that in equilibrium each firm chooses to report truthfully without receiving any subsidy. The use of competition may give rise to an efficiency loss due to the increasing returns to scale. However, we show that our mechanism may still be better, from a social welfare point of view, than the case of monopoly regulation that involves no subsidy.